Trauma Auschwitz: zu Verarbeitungen des Nichtverarbeitbaren bei Peter Weiss, Luigi Nono und Paul Dessau - Kontarsky, Matthias 1965- (Saarbrücken Pfau, 2001)
Examines musical compositions which were produced in concentration camps, besides works of composers who were tortured and murdered there. Queries whether and to what extent an examination of the "Auschwitz trauma" is feasible, exploring as a model Luigi Nono's composition "Ricorda cosa ti hanno fatto in Auschwitz", an incidental music composed for the play "Ermittlung" by Peter Weiss, which is based on the Auschwitz trials. Step by step, reconstructs the literary-musical relief from the crime to the piece of art. Compares Nono's play, also, with a composition by Paul Dessau, written as reaction to a wave of antisemitism in Germany in 1959. Discovers, besides expected differences, also a common ground. Concludes, finally, that an artistic coping with Auschwitz necessarily evokes certain resembling mechanisms.
Originally presented as the author's thesis (Ph. D.)--Universität Wien, 1999.
Includes bibliographical references (p. 184-193).
Keywords: Weiss, Peter -- 1916-1982; Nono, Luigi -- 1924-1990; Dessau, Paul -- 1894-1979; Holocaust; Composing